Implementasi Model Islamic Peace Education di SD Islam Ta’allumul Huda Bumiayu - Adnan Yusufi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: In many forms of bullying, a phenomenon in Indonesia increasingly lively happening, especially in education field. The concept of peace education is considered capable of being an alternative effort minimize violent acts. SD Islam Ta'allumul Huda Bumiayu is one of basic education institution focusing on the Islamic learning, mutual respect, tolerance and a sense of camaraderie in the absence of violence (Islamic Peace Education). The application of the model of Islamic peace education elementary school-based learning in the form of Islam that all activities in the school child is packed in a single education system. This research aims to find out and analyze design models of Islamic peace education in SD Islam Ta'allumul Huda Bumiayu while implementation as well as the supporting factors and constraints that exist. The approach considered suitable for this type of research is descriptive qualitative. The results of this research obtained information that the design model of Islamic peace education applied in SD Islam Ta'allumul Huda Bumiayu is a result of the integration between education curriculum 2013 Kemdikbud with Kemenag RI packed in learning Islamic-based elementary school. Implementation of the model is carried out through three main activities, namely intracurricular, cocurricular and extracurricular activities with an example approach and conditioning as well as insightful integrative inclusive. Implementation in the form of activity planning, implementation and evaluation. As for the existing constituents include good cooperation among school with the Foundation or caregivers and surrounding communities. While the constraints faced by the inadequate quality of human resources are owned by the school and also the limitations of existing education facilities. Key Words: Bullying, Pendidikan Perdamaian Islami, dan Integrasi Kurikulum 2013